Hydrogen generation, storage, and utilization - Zhang, Jin Zhong; Li, Jinghong; Li, Yat.; Zhao, Yiping (Hoboken, New Jersey : Wiley-Science Wise., 2014)
'The potential use of hydrogen as a clean and renewable fuel resource has generated significant attention in recent years, especially given the rapidly increasing demand for energy sources and the dwindling availability of fossil fuels. Hydrogen is an'ideal fuel' in several ways. Its only byproduct of consumption is water; it is the most abundant element in the universe; and it is available at low cost. Hydrogen generation is possible via a number of possible chemical processes, to separate the hydrogen from its bond with atoms such as carbon, nitrogen, and oxygen. In this book, the authors provide the scientific foundations for established and innovative methods of hydrogen extraction; outline solutions for its storage; and illustrate its applications in the fields of petroleum, chemical, metallurgical, physics, and manufacturing.'--Unedited summary from book.
Includes bibliographical references and index.
Keywords: Hydrogen -- Storage; Energy storage; Hydrogen as fuel; TECHNOLOGY & ENGINEERING -- Power Resources -- General; Energy storage; Hydrogen as fuel; Hydrogen -- Storage; Electronic books; Electronic books